Utilization of Waste Rubber Materials After the End of Their Life Cycle in the Production of Three-Layer Particleboards—Physical and Mechanical Properties - Mancel, Vladimír; Čabalová, Iveta; Krilek, Jozef; Olgun, Çağrı; Öncel, Mustafa; Tor, Önder; Szul, Tomasz; Woroniak, Grzegorz; Piotrowska-Woroniak, Joanna (MDPI AG, 2025)
The aim of the article was to test new types of rubber-containing particleboards created from waste materials, which positively contributes to environmental protection, saving primary resources and reducing production costs. This article focuses on the study of three-layer particleboards made from wood particles (spruce non-treated beams) and waste rubber granulates (tires, mixture of seals and carpets, internal flammable cables, external non-flammable cables). Urea–formaldehyde glue, melamine–formaldehyde glue, paraffin emulsion, and ammonium nitrate were used as a binders and excipients in the manufacturing of particleboards. In the core layer of each particleboard, 10% of the weight was made up of rubber granulate. Physical properties (density, water absorption, thickness swelling) and mechanical properties (internal bonding strength, modulus of rupture, modulus of elasticity, screw driving torque) were assessed from this perspective using current EN technical standards. According to the findings, the average densities of all particleboards were comparable to each other in a range from 0.692 to 0.704 g·cm−3. The lowest average water absorption and thickness swelling reached particleboards containing 10% of waste internal flammable cables, namely 32.79% for water absorption and 13.21% for thickness swelling. The highest average internal bonding strength reached particleboards without rubber filler and particleboards containing 10% of waste external non-flammable cables, namely 0.52 MPa for both types. The highest average modulus of rupture reached particleboards without rubber filler, namely 12.44 MPa. The highest average modulus of elasticity reached particleboards containing 10% of waste internal flammable cables, namely 2206.29 MPa, and the highest screw driving torque reached particleboards without rubber filler, namely 0.46 N·m for seating torque and 1.44 N·m for stripping torque. The results show that particleboards containing waste external non-flammable cables and particleboards containing waste internal flammable cables achieved comparable results to particleboards without rubber filler, which provides a good basis for a new way of utilizing this type of waste in the form of producing new wood–rubber composites.
Keywords: Article